Plasmodium falciparum immunodominant IgG epitopes in subclinical malaria - Azcárate, Isabel G. (Sci Rep, 2020)
Incomplete non-sterile immunity to malaria is attained in endemic regions after recurrent infections by a large percentage of the adult population, who carry the malaria parasite asymptomatically. Although blood-stage Plasmodium falciparum rapidly elicits IgG responses, the target antigens of partially protective and non-protective IgG antibodies as well as the basis for the acquisition of these antibodies remain largely unknown. We performed IgG-immunomics to screen for P. falciparum antigens and to identify epitopes associated with exposure and clinical disease. Sera from malaria cases identified five prevalent antigens recognized by all analyzed patients’ IgGs. Epitope mapping of them, using adult and children sera samples from an endemic malaria region in Ghana segregated into patients with positive or negative subclinical detection of P. falciparum, revealed binding specificity for two 20-mer immunodominant antigenic regions within the START-related lipid transfer protein and the protein disulfide isomerase PDI8. These 20-mer epitopes challenged with sera samples from children under 5 years old displayed specific IgG binding in those with detectable parasitemia, even at subclinical level. These results suggest that humoral response against START and PDI8 antigens may be triggered at submicroscopic parasitemia levels in children and may eventually be used to differentially diagnose subclinical malaria in children.